Anti-β2GPI-domain I antibody is associated with extra-criteria manifestations in a large prospective antiphospholipid syndrome cohort in China - Xiaofeng Zeng; Qian Wang; Jiuliang Zhao; Xinping Tian; Mengtao Li; Chaojun Hu; Can Huang; Yangzhong Zhou; Wanting Qi; Yin Long (Lupus Science and Medicine, 2023)
Background Anti-β2GPI-domain I (β2GPI-DI) antibody is pathogenic in patients with antiphospholipid syndrome (APS), but its additional clinical associations and diagnostic value are controversial.Methods A total of 378 patients were included, of which 119 patients diagnosed with primary APS, 50 with APS secondary to SLE (SAPS group), 209 with SLE without APS (SLE group). Serum anti-β2GPI-DI IgG was measured using chemiluminescent immunoassay. Extra-criteria manifestations were analysed, including thrombocytopenia, autoimmune haemolytic anaemia, valvular lesions, APS nephropathy and non-vascular neurological manifestations.Results In 169 patients with APS, 55 (32.5%) were positive for anti-β2GPI-DI IgG, accounting for 77.5% of those with anti-β2GPI IgG positivity. It is shown that 96.4% of those with anti-β2GPI-DI IgG also showed triple positivity in classic antiphospholipid antibodies (aPLs). The positivity of anti-β2GPI-DI IgG was significantly associated with recurrent thrombosis before APS diagnosis (p=0.015), microvascular thrombosis (p=0.038), but not with pregnancy morbidity (PM). Notably, patients with extra-criteria manifestations showed significantly higher positivity (p=0.001) and titres (p<0.001) in anti-β2GPI-DI IgG, especially for thrombocytopenia and APS nephropathy. In multivariable analysis, anti-β2GPI-DI IgG positivity (OR 2.94, 95% CI 1.29 to 6.70), secondary APS, arterial hypertension and Coombs’ test positivity independently predicted extra-criteria manifestations (C-index 0.83, 95% CI 0.77 to 0.90). After a median follow-up of 25 months, patients with anti-β2GPI-DI IgG also showed a tendency of more extra-criteria events, but not thrombotic events. Anti-β2GPI-DI was positive among 8.1% of the SLE controls, and showed high specificity (91.9%) in diagnosing SAPS among patients with SLE as compared with classic aPLs.Conclusion Anti-β2GPI-DI IgG was associated with extra-criteria manifestations in patients with APS. Further studies are warranted to validate its predictive values and potential role in daily practice.